First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations THE PEOPLE'S LEAGUE OF HEALTH. BALANCE SHEET, from 13th February, 1919, to 30th June, 1920. LIABILITIES. CREDITORS— £ s. d. £ s. d. Rent to June 30th, 1920 40 10 0 Caretaker's Expenses 10 2 Electric Light 12 0 Salaries 1 0 0 "Times" 1 0 0 Leicester Branch 14 8 0 58 0 2 GUARANTEE FUND SUBSCRIPTIONS 113 13 0 BALANCE OF INCOME AND EXPENDITURE ACCOUNT 363 8 10 £535 2 0 ASSETS. £ s. d. £ s. d. TYPEWRITERS — At Cost 36 8 6 TELEPHONE — Paid in advance 7 11 8 CASH AT BANKERS — London County, Westminster and Parr's Bank, Ltd., Hanover Square — No. 1 Account 111 2 5 No. 2 Account 9 16 5 Deposit Account 170 0 0 290 18 10 NATIONAL HEALTH INSURANCE STAMPS — In Hand 3 0 SUNDRY DEBTORS for Subscriptions and Donations 200 0 0 £535 2 0 (Signed) F.N. CURZON, Hon. Treasurer. „ OLGA NETHERSOLE, Hon. Organiser. „ E.M. WHITE, Secretary. REPORT OF THE AUDITORS. — We have examined the foregoing Account of Income and Expenditure and the above Balance Sheet, with the books and vouchers, and have obtained all the information and explanations we have required. In our opinion the Balance Sheet is property drawn up so as to exhibit a true and correct view of the state of the League's affairs according to the best of our information and the explanations given to us as shown by the Books. 3, CROSBY SQUARE, E.C.3. (Signed) EDWARD MOORE & SON, Chartered Accountants. July 15th, 1920 Honorary Auditors. 200/B/3/2/C693/1/71